THE IMPACT OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL STRUCTURE, AND JOB-SATISFACTION ON HIGH SCHOOL TEACHERS’ JOB-PERFORMANCE - Wesly Hutabarat (Jurnal Cakrawala Pendidikan, 2015)
Abstract: This study was a causal espouse fact study intended to find out and uncover direct and indirect effects of organizational culture, organizational structure, and job-satisfaction on teachers’ jobperformance. The sample consisting of 143 out of 645 public high school teachers were selected from 10 senior high schools by using the stratified random sampling technique. The teachers were those having teaching experience of at least 10 years and they had been certified as professional teachers and received certification fees continuously, except for guidance and counseling teachers. The findings showed that organizational culture, organizational structure and job-satisfaction had a positive impact on teachers’ job-performance. The direct and indirect effects of organizational culture on job-satisfaction were 21.20%, and 10.00% respectively. The direct and indirect effects of organizational culture on job-performance were 23.20% and 22.80% respectively. The direct effect of organizational structure on job-performance was 29.50%. Meanwhile, the indirect effect of organizational structure on job-performance was not significant. Finally, the direct effect of job-satisfaction on job-performance was 18.60%. Keywords: organizationa culture, organizational structure, job-performance, job-satisfaction DAMPAK BUDAYA ORGANISASI, STRUKTUR ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMA Abstrak: Penelitian ini merupakan penelitian kausal espouse facts yang dimaksudkan untuk meng- ungkap efek langsung dan tidak langsung budaya organisasi, struktur organisasi, dan kepuasan kerja terhadap kinerja. Sampel terdiri atas 143 dari 645 guru SMA yang diambil dari 10 SMA di Medan yang diambil dengan teknik stratified random sampling techmiques. Sampel guru paling tidak memiliki pengalaman mengajar 10 tahun dan telah disertifikasi sebagai guru profesional. Data dianalisis dengan teknik regresi dan sebelumnya telah diuji normalitas dan linearitas sebarannya. Temuan penelitian menunjukkan bahwa budaya organisasi, struktur organisasi dan kepuasan kerja memberi dampak positif terhadap kinerja guru SMA Kota Medan. Pengaruh langsung dan pengaruh tidak langsung budaya organisasi terhadap kepuasan kerja masing-masing 21,20%, dan 10,00%. Efek langsung dan tidak langsung budaya organisasi terhadap kinerja masing-masing 23,20% dan 22.80%. Efek langsung dari struktur organisasi terhadap kinerja ada 29,50%, sedangkan pengaruh tidak langsung dari struktur organisasi terhadap kinerja tidak fignificant. Akhirnya, efek langsung dari kepuasan kerja terhadap kinerja ada 18,60%. Kata Kunci: budaya organisasi, struktur organisasi, kepuasan kerja, kinerja